Laxmi Prasad Devkota: A Myth-taker and a Myth-maker - Adhikari, Tara Prasad (Literary Studies, 2020)
Laxmi Prasad Devkota was a romantic poet, well acquainted with the Western and Eastern romantic tradition. It is a well-known fact that the western romantic writers brought about a kind of revival of the era of mythology through their writings. Mythical stories and scenes often became the sources for their works. These romantic poets sometimes took the existing myths for their literary creations and sometimes they also created their own myths. Love for mythology is visible not only in these western Romantic poets but also in our own poet, Mahakavi Devkota. Because of his intense knowledge of the classic myths, he often exploits some aspects of mythology in his writings. In his works, Devkota often uses mythological refrains, names, character traits, mythical beings and some related images. He does not just take myths from various sources; at times he also creates them.